Imagine you derive the following expression by analyzing the physics of a particular system: M= (mv2r)(mGr2). Simplify the expression for M using the techniques mentioned above.

Respuesta :

Answer:

The simplified expression is [tex]M = \frac{v^2 r}{G}[/tex]

Explanation:

From the question we are told that  

     [tex]M = \frac{ \frac{m v^2}{r} }{\frac{ mG}{r^2 } }[/tex]

So simplifying we have

    [tex]M = \frac{m v^2}{r} * \frac{r^2 }{ mG }[/tex]

    [tex]M = \frac{v^2 r}{G}[/tex]

Thus the simplified formula is [tex]M = \frac{v^2 r}{G}[/tex]

ACCESS MORE